The Copulation duration Allometry in Centrobolus (Diplopoda: Spirobolida: Pachybolidae) - Mark Cooper (New Visions in Biological Science Vol. 9, 2022)
Of the determining factors of copulation duration across arthropods, I reviewed copulation duration variance in forest millipedes. The objective was to calculate the variance in copulation duration. The null hypothesis was mean copulation duration and copulation duration variance were independent of body mass. Copulation duration and standard deviation squared for 4 populations of millipedes were seen in the literature. Copulation duration correlated with it’s variance (r=0.95, r2=0.90, n=5, p=0.01). Durations ranged from C. anulatus (34.9 minutes) to C. inscriptus (303 minutes) Female mass was correlated to copulation duration variance (r=0.95, z-score=1.86, n=4, p=0.03). Millipedes were similar to some arachnids where the duration of copulation and variance in copulation duration correlated with intra-specific size variation. Female mass correlated to copulation duration (r=0.99, z-score=2.71, n=4, p<0.01). Sexual size dimorphism (SSD) was related to male mass (r=-0.97, z-score=-2.17, n=4, p=0.01). Prolonged copulation duration was interpreted to have correlated with the intensity of sperm competition and female control of copulation duration. Females control the duration of copulation based on mass.